Experimental and numerical study of CO2 adsorption on copper benzene-1, 3, 5-tricarboxylate (Cu-BTC) metal organic framework. (January 2016) - Wang, H.; Qu, Z.G.; Zhang, W.; Yu, Q.N.; He, Y.L.
Highlights: The amount and isosteric heat of CO2 adsorption in Cu-BTC are experimentally studied. A numerical model is proposed to predict the CO2 adsorption amount and isosteric heat. The Lennard-Jones potential makes dominant contribution for the CO2 adsorption. The L-J potential controls the adsorbed CO2 in the tetrahedron-shaped pockets of Cu-BTC. Electrostatic interactions contribute to the larger square-shaped channels. Abstract: The amount and isosteric heat of CO2 adsorption in copper benzene-1, 3, 5-tricarboxylate (Cu-BTC) metal organic framework are synchronously experimentally studied with the combined PCTProE&E and Calvet Calorimeter under the ambient temperature of 35 °C and pressure range 0–1200 kPa. A grand canonical Monte Carlo numerical model is proposed to predict the CO2 adsorption amount combined with isosteric heat. The numerical model is validated with experimental data, and the obtained adsorption snapshots can provide a deep insight for the adsorption structure at molecular level. The CO2 adsorption amount and heat have three contributions: the Lennard-Jones potential, electrostatic interactions between CO2 and Cu-BTC, and electrostatic interactions between CO2 and CO2 . The contribution rate ranges for the adsorption amount of the three mechanisms are 48.45–69.66%, 28.43–48.41%, and 1.91–3.14%, respectively. The third contribution can be ignored. The L-J potential controls the adsorbed CO2 molecules in the tetrahedron-shaped pockets of Cu-BTC, whereas the electrostatic interactions between CO2 and Cu-BTC control the adsorbed CO2 molecules in the larger square-shaped channels of Cu-BTC.